2017
DOI: 10.18632/oncotarget.14783
|View full text |Cite
|
Sign up to set email alerts
|

Integrative miRNA and mRNA analysis in penile carcinomas reveals markers and pathways with potential clinical impact

Abstract: Penile carcinoma (PeCa) is an important public health issue in poor and developing countries, and has only recently been explored in terms of genetic and epigenetic studies. Integrative data analysis is a powerful method for the identification of molecular drivers involved in cancer development and progression. miRNA and mRNA expression profiles followed by integrative analysis were investigated in 23 PeCa and 12 non-neoplastic penile tissues (NPT). Expression levels of eight miRNAs and 10 mRNAs were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
46
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 58 publications
10
46
2
Order By: Relevance
“…1,11,12 Other molecular mechanisms have been described, including new targets of E6 and E7 oncoproteins, which might interact or modulate the activity of proteins involved in the epigenetic regulation or in the differential expression of host cell miRNAs. [13][14][15][16][17] In parallel, the chronic inflammatory process has been investigated as a risk factor to PeCa, which can be triggered by phimosis, lichen sclerosus, and balanitis. [18][19][20][21] This process can provide a favorable microenvironment for malignant cell transformation and progression due to the release of reactive oxygen or nitrogen species, as well due to the extensive tissue damage and remodeling that is mediated by the immune system cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,11,12 Other molecular mechanisms have been described, including new targets of E6 and E7 oncoproteins, which might interact or modulate the activity of proteins involved in the epigenetic regulation or in the differential expression of host cell miRNAs. [13][14][15][16][17] In parallel, the chronic inflammatory process has been investigated as a risk factor to PeCa, which can be triggered by phimosis, lichen sclerosus, and balanitis. [18][19][20][21] This process can provide a favorable microenvironment for malignant cell transformation and progression due to the release of reactive oxygen or nitrogen species, as well due to the extensive tissue damage and remodeling that is mediated by the immune system cells.…”
mentioning
confidence: 99%
“…Interestingly, in our study, the ADAM6 member was observed amplified in 100% of the PeCa analyzed, reinforcing the involvement of EGFR, and matrix metalloproteinase pathways in PeCa. 15 Considering that the majority of the tumors was positive for hrHPV, it is worth noting that the HPV oncogene E5 product is a transmembrane protein that regulates activation of EGFR, which leads to a decrease in E-cadherin expression and it is also associated with increase in matrix metalloproteinase (MMP)-9, resulting in decreased cell-to-cell adhesion. 60 Peta et al 61 showed that EGFR overexpression in PeCa can be mediated by high-risk HPV E6 through downregulation of miR-146a.…”
mentioning
confidence: 99%
“…Molecular alterations in PeCa have been described only recently by our group and others [19,[21][22][23][24][25][26][27][28][29][30]. Interestingly, contrary to the findings described in breast and prostate cancers, AR mRNA is down-expressed in PeCa [19]. Moreover, AR alteration was pointed out as one of the main putative drivers in PeCa [28].…”
Section: Introductionmentioning
confidence: 69%
“…Penile cancer is a rare disease in developed countries; however, it is more common in poor regions [12]. The human papillomavirus (HPV) infection has been described in 22.2 to 63% of penile carcinomas [13][14][15][16][17][18][19], being the HPV16 the predominant type. The large range of the HPV positivity among different studies may be due to sampling methods, HPV detection procedures, histopathological subtypes, and population cohorts [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation